Removal of Arsenic from Water using Hybrid SLM-Electrocoagulation Technique - Sarkar, Soumi (My University, 2024)
This research focuses on a novel hybrid technique combining supported liquid membrane (SLM) separation with electrocoagulation for effective arsenic removal from water. Utilizing sesame oil, an environmentally benign solvent, and Aliquat® 336, the study developed a pseudo-binary liquid membrane system. The work includes comprehensive physicochemical analysis and molecular modelling of the membrane system. It reveals that As(V) is more favourable for extraction due to its larger ionic size and higher positive charge compared to As(III). Two-phase equilibrium studies and advanced statistical and machine learning models, including artificial neural networks and genetic algorithms, optimized the extraction process. A three-phase SLM setup demonstrated efficient separation and recovery of arsenic species, with performance enhanced by synergistic effects between As(III) and As(V).
Saha, Prabirkumar